2022
DOI: 10.1021/acs.jpcb.1c10834
|View full text |Cite
|
Sign up to set email alerts
|

R–D–A and R–D−π–A Structured AIEgens: Relationship between Electronic, Conformational Characteristics and Photophysical Properties

Abstract: The design of new aggregation-induced emission luminogens (AIEgens) has aroused continuous attention. The relationship between structure and performance plays an important role in guiding such efforts. In this contribution, two R−D−A-and R−D−π−A-type AIEgens were facilely designed and synthesized, that is, DPE-PTZ-CN and DPE-PTZ-PCN, with diphenylethylene as the twisted rotor structure (R), phenothiazine as electron-donor (D), and the (aryl) cyano group as electron-acceptor (A) fragments. Both luminophores wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The past few decades have witnessed unprecedented progress in development of tools for ATP detection, including small molecule probes, [7] luciferin‐luciferase bioluminescent techniques, [8] and genetically encoded sensors [9] . In particular, anti‐ATP aptamer, first screened by Huizenga and Szostak in 1995, [10] was engineered into ATP biosensors via structure‐switching design, [11] which provides a powerful platform for ATP detection in test tubes [12–14] and ATP imaging in live cells [15–22] .…”
Section: Introductionmentioning
confidence: 99%
“…The past few decades have witnessed unprecedented progress in development of tools for ATP detection, including small molecule probes, [7] luciferin‐luciferase bioluminescent techniques, [8] and genetically encoded sensors [9] . In particular, anti‐ATP aptamer, first screened by Huizenga and Szostak in 1995, [10] was engineered into ATP biosensors via structure‐switching design, [11] which provides a powerful platform for ATP detection in test tubes [12–14] and ATP imaging in live cells [15–22] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sophisticated technologies such as protein purification, genetic engineering, and bioconjugation are required to construct those biosensors. In this context, readily‐available small‐molecule probes that bind ATP reversibly have been sought after very recently, leading to a handful number of fluorescent probes up to date [11, 12] . Furthermore, by introducing a proper organelle‐targeting moiety, some fluorescent probes that selectively detect ATP in mitochondria, [13–16] lysosomes, [17, 18] and cell membranes, [13] as well as in cytoplasm [19–22] have been also developed (Figure 1, Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, TiCl 4 is known as a predominant chemical dealcoholating agent 24,25 . Actually, even though here there are few reports using other Lewis acid compounds, such as triethylaluminum 26–28 and Cl 2 (CH 3 ) 2 Si, 27 there are many published papers based on alkyl aluminum dealcoholation for the MgCl 2 ·EtOH adduct, including among others the work of Chadwick together with Severn 29–34 and Huang 35–38 or separately 39,40 . Interestingly, preliminary results showed that while chemical delacoholation by triethylaluminum furnishes a super active Ziegler–Natta catalyst, it completely destroys the morphology of the catalyst, corresponding to the aggressive interaction of this chemical with ethanol molecules 26 .…”
Section: Introductionmentioning
confidence: 99%